Automatic Fitting of a Deformable Face Mask Using a Single Image - Kuhl, Annika; Tan, Tele; Venkatesh, Svetha (Springer, 2009)
We propose an automatic method for person-independent fitting of a deformable 3D face mask model under varying illumination conditions. Principle Component Analysis is utilised to build a face model which is then used within a particle filter based approach to fit the mask to the image. By subdividing a coarse mask and using a novel texture mapping technique, we further apply the 3D face model to fit into lower resolution images. The illumination invariance is achieved by representing each face as a combination of harmonic images within the weighting function of the particle filter. We demonstrate the performance of our approach on the IMM Face Database and the Extended Yale Face Database and show that it out performs the Active Shape Models approach.